Novel Complex Unbalanced Dicentric X-Autosome Rearrangement in a Thoroughbred Mare with a Mild Effect on the Phenotype - Mendoza, M. N. (2020)
Complex structural X chromosome abnormalities are rare in humans and animals, and not recurrent. Yet, each case provides a fascinating opportunity to evaluate X chromosome content and functional status in relation to the effect on the phenotype. Here, we report the first equine case of a complex unbalanced X-autosome rearrangement in a healthy but short in stature Thoroughbred mare. Studies of about 200 cells by chromosome banding and FISH revealed an abnormal 2n=63,X,der(X;16) karyotype with a large dicentric derivative chromosome (der). The der was comprised of normal Xp material, a palindromic duplication of Xq12q21, and a translocation of chromosome 16 to the inverted Xq12q21 segment by the centromere, whereas the distal Xq22q29 was deleted from the der. Microsatellite genotyping determined a paternal origin of the der. While there was no option to experimentally investigate the status of X chromosome inactivation (XCI), the observed mild phenotype of this case suggested the following scenario to retain an almost normal genetic balance: active normal X, inactivated X-portion of the der, but without XCI spreading into the translocated chromosome 16. Cases like this present unique resources to acquire information about species-specific features of X regulation and the role of X-linked genes in development, health, and disease.